Revisiting and re-representing scaffolding: The two gradient model - Shoaib Ahmed Malik (Cogent Education, 2017)
In this paper I intend to illustrate Vygotsky’s Zone of Proximal Development (ZPD) and then extend the discussion to scaffolding and its relationship with the ZPD. This is then followed by some concerns raised in literature regarding scaffolding as a concept and as a metaphor which involves analysing the arguments for regarding the role of cultural tools and peers as scaffolds akin to instructors. In consideration of some of the criticisms directed at scaffolding, I introduce the concept of the Two Gradient Model (TGM) which is a descriptive model that attempts to clarify the interaction between the instructor and learner. Furthermore, the TGM also demonstrates the need to differentiate between instructors and cultural tools as scaffolds where the latter should be kept relegated as secondary components in the scaffolding process. Additionally, the TGM also differentiates between instructors and peers whereby the latter do not occupy the same interpersonal dynamics as the former in a pedagogical environment.